Biomass flows and defoliation patterns of alexandergrass pasture grazed by beef heifers, receiving or not protein salt - Eloy, Lidiane Raquel; Rocha, Marta Gomes da; Pötter, Luciana; Salvador, Paulo Roberto; Stivanin, Sheila Cristina Bosco; Hampel, Viviane da Silva (Acta Scientiarum. Animal Sciences, 2014)
The experiment aimed at evaluating leaf biomass flow, intensity and frequency of defoliation of Alexandergrass (Urochloa plantaginea (Link) Hitch) by beef heifers exclusively on pasture or that grazed and received protein salt. A completely randomized experimental design was used with repeated measures over time, two treatments and two area replications, with three Angus test heifers by paddock. Leaf blade intake flow is 18% superior for heifers exclusively on pasture. Grazing intensity (59.8%) is similar when heifers receive protein salt or not. Heifers receiving protein salt reduce by one day the defoliation frequency of tillers. The supply of protein salt for beef heifers grazing Alexandergrass affects the herbivore-plant relationship, decreasing intake flow and leaf blade defoliation frequency.